Intuitive versus Contemplative: Do Entrepreneurs differ in their Decision-Making Style from Managers and Employees? - Martin Koudstaal; Randolph Sloof; Mirjam (C.M.) van Praag (Tinbergen Institute, 2017)
We examine in a large survey (n = 1,928) how contemplative entrepreneurs, managers and employees are in their decision making styles. Besides two well-known subjective measures taken from psychology, we also build on Rubinstein (2016) by including two objective measures derived from response times and the nature of the strategic choices made. Supporting conventional wisdom, we find that entrepreneurs have a stronger subjective Faith in Intuition than others. Their actual action choices are partly in line with this: entrepreneurs make indeed more intuitive choices than managers, but are equally intuitive as employees. At the same time entrepreneurs have response times and a subjective Need for Cognition that (on average) equal those of managers. Together these findings tentatively suggest that entrepreneurs start from a stronger prior intuition, making them ceteris paribus more intuitive than others, but at the same time share with managers a higher need for cognition, and thus take more time to think things over.
Keywords: L26; C93; D91; M13; 330; Response times; contemplativeness; faith in intuition; need for cognition; entrepreneurs; managers; lab-in-the-field experiment